Assessment of Egg Hatchability and Spawn Survival of Deccan Mahseer, Tor Khudree (sykes, 1839) at Different Levels of Water PH - S. R. Kalbande; V. R. Bhatkar; A. S. Pawase; S.D. Naik; M.S. Sawant; P.R. Kalbande (Journal of Indian Fisheries Association, 2022)
The present study was undertaken to evaluate assessment of egg hatchability and spawn survival of Deccan mahseer, Tor khudree (Sykes, 1839) at different levels of water pH. The fertilized eggs of Tor khudree with a size ranging from 2.5 mm to 2.7 mm were kept for incubation in 500 L FRP tank inside the rectangular floating plastic trays (31.5 x 23 x 10.5 cm). The eggs were kept to the different treatment groups at a rate of 120 no. Tray-1. The experiments were conducted as per the Completely Randomized Design with six treatments having four replications. The experiment, was carried out to determine the optimum range of ph for egg incubation and hatching of Deccan mahseer, Tor khudree. The fertilized eggs were reared with six different water ph treatments such as T0 (6-pH), T1 (6.5-pH), T2 (7-pH), T3 (7.5-pH), T4 (8- pH) and T5 (8.5-pH). Higher egg diameter (3.2 ±0.68 mm), incubation period (49 ± 0.41 h), length of spawn (12.15 ± 0.33 mm), fertilization rate (94.75 ± 0.85 %) and post-hatch survival rate (88.75 ± 2.02 %) were observed in treatment T4 (8- pH). Significant difference was observed in egg diameter, incubation period, length of spawn, fertilization rate and post-hatch survival rate. Similar hatching rate (99.5 ± 0.29) was observed in treatment T3 (7.5-pH), T4 (8- pH) and T5 (8.5-pH). Water ph level was found suitable for egg diameter (after water absorption), incubation period and fertilization rate, post-hatch survival rate and spawn length gain. The pH ranging from 7.5 to 8.5 was found more suitable for hatching of Tor khudree pH eggs.